(untitled) (NOURA: Jurnal Kajian Gender dan Anak, 2024)
This article discusses the urgency of understanding gender in children in shaping a quality personality. Understanding gender in children is very important because it can help them develop an open and critical mindset and increase their self-awareness. The preparation of this article uses a literature review through a qualitative approach with a descriptive-analytic nature. This method is carried out by collecting, studying and analysing various literature, books, journals, papers and other sources of information relevant to the topic under study. Therefore, this article concludes that understanding gender in children is crucial in shaping a quality personality and creating a more inclusive and fair society for everyone. Understanding gender can help children better understand themselves and others, strengthening their identity and confidence. In addition, understanding gender can also help children understand and overcome gender discrimination and stereotypes that still exist in society. This can help children become more tolerant, wise and able to adapt to the changes around them.